The relationship between skeletal muscle mass and cardiac structure in elderly male inpatients - Lingyan Chen; Le Song; Xi Li; Yu Hu; Man Luo (Frontiers in Cardiovascular Medicine, 2026)
Introduction To investigate the associations of skeletal muscle mass index (SMI) and handgrip strength with cardiac structure and function in elderly male inpatients without severe acute cardiovascular conditions. Methods This cross-sectional study included 143 male inpatients aged ≥60 years. SMI was assessed using dual-energy x-ray absorptiometry, handgrip strength was measured by electronic dynamometry, and cardiac structure and function were evaluated by two-dimensional echocardiography. Multivariable linear regression and restricted cubic spline models were performed to assess the associations between skeletal muscle characteristics and echocardiographic parameters. Results Compared with the normal-SMI group, participants with low SMI had significantly smaller ARD, LVEDD, and LVESD (all P < 0.05). In fully adjusted models, SMI remained independently associated with ARD ( β = 0.131, P = 0.048), LVEDD ( β = 0.135, P = 0.032), LVESD ( β = 0.152, P = 0.013), and LVEF ( β = 0.130, P = 0.035). Handgrip strength was independently associated only with ARD ( β = 0.283, P = 0.009). Restricted cubic spline analyses demonstrated linear associations between SMI and left ventricular parameters (all P for non-linearity > 0.05). Subgroup analyses showed consistent associations across predefined strata without significant interactions. Discussion In elderly male inpatients, SMI was independently and linearly associated with left ventricular structure and systolic function, whereas handgrip strength showed fewer significant associations with cardiac parameters. These observational findings suggest that SMI may represent a potential marker of age-related left ventricular structural changes; however, longitudinal studies are required to determine the temporal relationship and clinical implications.